Effect of surfactants on Aspergillus brasiliensis ATCC 16404 physicochemical properties. Issue 2 (April 2018) - Hamzah, Nurhidayah; Singhal, Naresh; Padhye, Lokesh; Swift, Simon
Abstract: This study investigates the adsorption of Rhamnolipid and TritonX-100 on the dense layered mycelium and hydrophobic fungi surface, A. brasiliensis to evaluate the adsorption isotherm and mechanism of the anionic and non-ionic surfactant on hydrophobic surface of fungal pellet. The mechanisms were determined by thermodynamic theory principals of surface tension and surface free energy to support the adsorption result. The change of cell surface hydrophobicity of hyphae due to surfactants adsorption was also assessed using contact angle measurements (CAM). The adsorption isotherm was fitted to Freundlich Equation with the TritonX-100 adsorbed 20% less than Rhamnolipid and shows lower Kf value. For 1 g of fungus dry weight, A. brasiliensis adsorb 1602 ± 103 μg of TritonX-100 at 0.5 CMC and at 1.0 CMC of Rhamnolipids, 1651 ± 274.8 μg of Rhamnolipids was adsorbed to successfully modify the fungi surface hydrophobicity. The CAM analysis shows A. brasiliensis became hydrophilic with respect to the concentration of both surfactants. The hydrophobic interaction was the main driving force for the adsorption of surfactants on the fungi surfaces. The present study is expected to clarify the mechanism in which surfactants influenced the aggregation of dense mycelium and provides guidelines for surfactants enhanced biodegradation using fungi.